Tanggungjawab Pelaku Usaha di Marketplace Shopee Atas Refund tidak Terealisasi: Perspektif Kompilasi Hukum Ekonomi Syariah - Atika Farha Siregar; Sahliah Sahliah (Universitas Medan Area, 2023)
One common occurrence in online buying and selling is that the item may be damaged or not match the description provided. Shopee, a marketplace, offers a refund feature for consumers to return the goods or request a refund if this happens. However, not all refunds are successful. The aim of this study is to determine the factors that contribute to unsuccessful refunds and to examine the responsibilities of business actors in the shopee marketplace for refunds that are not realized according to the principles of sharia economic law. The research approach used in this study is empirical research with both the Living Care Studies Approach and Conceptual Approach approaches. The research is of a descriptive nature, and data was collected through observation and interviews. The findings indicate that the reason for unsuccessful refunds is the lack of responsibility of business actors. According to the Compilation of Sharia Economic Law, business actors must be held accountable for refunds that are not realized. Article 38 of the law outlines various forms of responsibility, such as paying compensation, cancelling contracts, transferring risk, imposing fines, and paying court fees. When a consumer requests a refund and does not receive the full amount paid for the goods or receives no payment at all, Shopee and the seller should refund the consumer the amount corresponding to the cancellation of the sale or purchase, or provide a replacement for the damaged item with a new item. Therefore, Shopee should pay attention to the policy regarding refunds for online buying and selling transactions to ensure that neither party is harmed, particularly consumers.